Pengaruh Rapat Arus Proses Continuous Hard Anodizing Elektrolit (H2SO4) terhadap Laju Korosi Pipa Aluminium 6061 dengan Pengujian Kabut Garam - Mochamad Muzaki; Endi Sutikno; Putu Hadi Setyorini (Polinema Press, Politeknik Negeri Malang, 2019)
Anodizing is an electro-chemical process used to coat metal surfaces with a stable oxide layer. The function of this oxide layer is to increase corrosion resistance. The purpose of this study is determine the effect of variations in current density on the continuous hard anodizing process carried out in sulfuric acid electrolyte solution (H2SO4) on the corrosion rate of aluminum alloy 6061. Corrosion rate testing is carried out through salt fog testing. The values of the current variation used are 1 A/dm2; 2 A/dm2; 3 A/dm2; 4 A/dm2; and 5 A/dm2. Statistical calculations using the analysis of variance proved the current density in the anodizing process has a significant effect on the corrosion resistance of the anodizing workpiece. Corrosion testing provides information that the highest corrosion rate is an anodizing workpiece with a current density of 1 A/dm2, which is 125.6861 mdd, then 2 A/dm2 of 104.33333 mdd. The lowest corrosion rate value obtained at the use of current density 3 A/dm2, that is 51,8083 mdd. Meanwhile, the use of current density of 4 A/dm2 has a slightly higher corrosion rate compared to the use of current density of 3 A/dm2, which is 86.5444 mdd. Furthermore, the use of current density of 5 A/dm2 has the highest decay rate, so that the formed oxide layer will be damaged, as seen from the higher corrosion rate of the material, which is 100.8361 mdd.